Pistachio Green Hull Extract Induces Apoptosis through Multiple Signaling Pathways by Causing Oxidative Stress on Colon Cancer Cells - Koyuncu, İsmail and Gönel, Ataman and Temiz, Ebru and Karaoğul, Eyyüp and Uyar, Zafer (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Pistachio is considered to be one of the fifty foods with the highest antioxidant effect. However, the anticancer effect mechanisms of this plant extracts are unknown. Objective: The aim of this study was to investigate the anticancer effect of different extracts from the green hull of pistachio. Methods: The cytotoxic effects of different solvent extracts on cancer and normal cells were examined by cell viability assay and flow cytometric analysis. The levels of the apoptotic gene and protein were investigated by Western Blot and ELISA, and qPCR. The intracellular free radical exchange was determined by oxidative and nitric oxide analyses. DNA damage level was measured by the 8-OHdG test. Phenolic and free fatty acid components were examined by LC-MS/MS and GC-MS, respectively. Results: It was determined that the n-hexane fraction showed a higher cytotoxic effect on cancer cells. Oxidative and cell cycle analyses indicated that the n-hexane fraction arrested cell cycle of HT-29 at the sub-G1 phase by increasing DNA damage through oxidative stress. In addition, gene expression analysis of the HT-29 treated with the n-hexane fraction indicated that apoptotic and autophagic gene expressions were significantly upregulated. LC-MS/MS analysis of the n-hexane fraction revealed the presence of 15 phenolic compounds, containing mainly gallic acid and catechin hydrate, and GC-MS analysis determined the presence of the following fatty acids: 9-octadecenoic acid, 9,12-octadecadienoic acid and hexadecenoic acid. Conclusion: Based on these grounds, we suggest that the n-hexane fraction of pistachio green hull damages DNA, arrests the cell cycle at the G1 subphase, and induces apoptosis through oxidative pathways in colon cancer.
Keywords: colorectal cancer